Trek-metod v diagnostike i trenirovke psikhomotorno-koordinatsionnykh sposobnostei v sannom sporte i bobslee - Loosch, E. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this paper was to discuss the opportunities of the new methodology to train and control the psychomotor- coordinational capacities of the athletes compeeting in sledge sport and bobsled. The significance of psychomotor -coordinational capacities tor the sports results in sledge sport and bobsled is shown in the article. The new method in the diagnosis and training of these capacities is offered.